What Athens Has to Do with Jerusalem: The Wisdom of Reason, the Publics of Theology - McDowell, John C. (Pacifica, 2009)
This paper, specifically composed to provide a vision for theology in the University of Newcastle NSW, offers a series of reflections that suggest first, that at present the very idea of a “university” is itself under pressure and in danger of becoming meaningless; secondly, that theology, conceived broadly through a pedagogical model of paideia, can engage in critical conversation over the identity of the university; and, thirdly, that theology, as a university discipline, can be properly ordered in terms of an ongoing conversation.